Diploma students’ perspective: pursue or not to pursue a degree in accountancy? - Awab, Nor’aini; Fatima, A.H. (2017)
This is an exploratory study which investigates the reasons influencing Diploma in Accountancy (DIA) students’ intention to pursue or not pursue a Bachelor of Accountancy (BAcc) degree programme. The Theory of Reasoned Action (TRA) is used as a basis for the study.The research involves collecting primary data through survey questionnaires.250 questionnaires were distributed to the final year DIA students in MARA Professional College. Based on the findings, the reasons that influence students’ intention to pursue are: the hope to earn a good salary, higher future earnings potential and greater employability in the future.In contrast, the reasons for non-pursuance of a BAcc programme are because students think that they can develop their potential for personal growth and career development with other degree programmes or they want to get jobs and start working after obtaining the DIA. These findings would be useful to the Ministry of Education, the universities as well as the professional bodies to ensure that the students continue their studies in the accounting discipline to achieve their full potential.